SEAKEEPING PREDICTION OF DEEP-V HIGH SPEED CATAMARAN USING COMPUTATIONAL FLUID DYNAMICS APPROACH - Ahmad Fitriadhy; Nur Amira Adam; N. Amalina; S. A. Azmi (SINERGI, 2018)
Seakeeping is the dynamic response of the ship in waves that may affect to passenger’s uncomfortability due to a harsh environmental condition.  Therefore, an extensive assessment of seakeeping performance in the initial step of ship design is necessarily required. The authors here proposed to analyze the seakeeping performance of ‘deep-V’ high speed catamaran using Computational Fluid Dynamics (CFD) approach. Several effects of Froude number (Fr), wave-length (